Penerapan Akad Murabahah Terhadap Pembiayaan KPR Perumahan Bersubsidi Di PT. Bank Sumut Syariah KCP. Lubuk Pakam - Gendis Raihan Ardha (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
A house is a basic human need, many people are rarely able to save in cash due to rising house prices. By providing pawn products (Home Ownership Credit), the Bank acts as a mediator between the interests of home buyers and sellers in this situation. However, Muslims are not allowed to use the usury transaction interest system used by mainstream banks. For Muslims who want interest-free financial services, the rise of Islamic banking is a good thing. However, the fact that sharia banking has not been able to match conventional banks in Indonesia is proof that the majority of Muslim communities there do not have full confidence in using sharia banks. Based on this, the author looks at and discusses how murabahah contracts are used in sharia finance at the Bank Sumut Syariah Lubuk Pakam Branch Office. The aim of this qualitative descriptive research which combines case study theory is to describe the implementation of the murabahah contract and determine its impact on sharia financing at Bank Sumut Syariah Lubuk Pakam Branch Office. To gather information regarding the use of murabahah contracts in Islam, the data collection approach uses interview procedures, namely questions and answers to officers, employees and authorized parties (in authority), as well as documentation. Descriptive techniques are used in data analysis procedures. The research findings, the application of the DSN-MUI fatwa regarding murabahah, turns out that the DSN-MUINo.04/DSNMUI/IV/2000 fatwa was followed in the case of murabahah financing for subsidized housing mortgage financing carried out by the North Sumatra Syariah Bank, Lubuk Pakam Branch Office.